George Shaw - a corner of a foreign field - Hallett, Mark 1965-; Lampert, Catherine 1946-; Mellor, David 1948-; Shinkle, Eugénie 1963-; Crow, Thomas E. 1948-; Deller, Jeremy 1966- (Yale University Press, 2018)
"Nominated for the Turner Prize in 2011, George Shaw (b. 1966) is one of Britain's leading contemporary painters, best known for his painstakingly detailed, luminous, and often elegiac representations of the British suburban landscape. Beautifully designed and generously illustrated, this book is the first to explore the entirety of Shaw's artistic output, which spans three decades. Beginning with his work at the Royal College of Art in the 1990s and ending with his most recent paintings, this volume places Shaw's work within the context of contemporary culture, from the traditions of English landscape painting to the repercussions of Brexit. An introductory essay and comprehensive catalogue texts by Mark Hallett are accompanied by essays on the artist's work by Tom Crow, Catherine Lampert, David Mellor, and Eugenie Shinkle. An interview between Shaw and the celebrated contemporary artist Jeremy Deller offers insight into this work from the perspective of the artist himself, while a fully illustrated chronology details the entirety of his career"...